Genotyping F1534C mutation on dried Aedes aegypti preparation through direct PCR method: a proof of concept - Perdana, Taufik Mulya; Wijaya, Yogik Onky Silvana; Dwiputro, Alfin Harjuno; Najla, Aesha; Taftazani, Muhammad Rifqi; Insani, Dini Aura; Pangesti, Rachma Widya; Satoto, Tri Baskoro Tunggul (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Aedes aegypti (Ae. aegypti) is the primary vector of dengue hemorrhagic fever (DHF). Various control strategies have been utilized to control its population, including the use of pyrethroid-based insecticides. However, the presence of mutations, such as the F1534C mutation, that confers resistance to pyrethroids has been increasingly reported. The increase of resistance-conferring mutation in Ae. aegypti population could potentially hinder DHF control measures. As such, monitoring the genotype of Ae. aegypti population is crucial. Mosquito rearing, DNA extraction, and PCR examination are usually employed to monitor the circulation of F1534C mutations. To simplify this process, we proposed a direct PCR workflow utilizing dried mosquito samples preserved on an in-house filter paper. To demonstrate the utility of our proposed workflow, we performed direct allele-specific PCR (AS-PCR) on 46 dried adult Ae. aegypti. As a comparator, conventional PCR was performed on 8 DNA extract from Ae. aegypti. Our results showed that direct AS-PCR successfully identified both wild-type (F allele) and mutant (C allele) genotypes from dried mosquitos with a success rate of 93.48%. These findings provide preliminary evidence supporting the use of cellulose-based in-house filter paper for genotyping insecticide-resistant mosquitoes. However, field testing must be performed before its implementation in real-world epidemiological and surveillance applications.